Women entrepreneurs: How power operates in bottom of the pyramid-marketing discourse. (September 2017) - Hopkinson, Gillian; Aman, Asad
The article explores hegemony in bottom-of-the-pyramid (BOP) marketing, specifically rural distribution schemes operated through women. Using Laclau and Mouffe's theory of discourse, the article considers the joint articulation of 'women entrepreneurs' through analysis of the Unilever Shakti system. It argues the discourse shapes subject positions, prescribes conduct and defines actors and the relationships between them. Discursive construction of entrepreneurs and empowered mothers obscures to an extent, economic aspects of the arrangement. It also imposes new forms of conduct without unsettling traditional hierarchies. Further research is needed in relating such schemes both to western forms of distribution and to other forms of market and models of distribution in BOP locations.